SPRAY DRIED AQUEOUS EXTRACT OF LEMONGRASS (Cymbopogon citratus) EXHIBITS IN VITRO AND IN VIVO ANTI HYPERGLYCEMIC ACTIVITIES - Maria Dewi Puspitasari Tirtaningtyas Gunawan-Puteri; Felicia Rustandi; Phebe Hendra (Sanata Dharma University, 2018)
Lemongrass was found to be a promising herb for anti-hyperglycemia treatment due to its activities to inhibit alpha glucosidase and alpha amylase in vitro activities and ability to improve blood glucose profile. Lemongrass potency through its anti-hyperglycemic ingredients requires evaluation of the functional stability during processing. In this study, the in vitro anti-hyperglycemic activities of spray-dried aqueous extract of lemongrass were determined by its inhibitory activity against rat intestinal glucosidase enzymatic hydrolysis of sucrose. In vivo activity was observed based on its ability to prevent blood glucose elevation in oral glucose, sucrose and maltose tolerance tests (OGTT, OSTT and OMTT). The in vitro evaluation showed that aqueous extraction, which involved stirring at 70 C for 40 min, successfully increased the glucosidase inhibitory activity of lemongrass extract, while spray drying with inlet 130 C had no significant impact to the activity tested in vitro. Spray-dried lemongrass powder was found to be effective for lowering blood glucose level in OGTT, OSTT and OMTT. This study provides support for further development of lemongrass extracts as functional ingredients for hyperglycemia treatment.